“Alexa, Can I Trust You?”. - Chung, Hyunji; Iorga, Michaela; Voas, Jeffrey; Lee, Sangjin (Computer (00189162), 2017)
Several recent incidents highlight significant security and privacy risks associated with intelligent virtual assistants (IVAs). Better diagnostic testing of IVA ecosystems can reveal such vulnerabilities and lead to more trustworthy systems.